1997
DOI: 10.1152/ajpheart.1997.272.4.h1615
|View full text |Cite
|
Sign up to set email alerts
|

Control of oxidative metabolism in volume-overloaded rat hearts: effect of propionyl-L-carnitine

Abstract: The objective of the present work was the assessment of metabolic events responsible for the improvement of hemodynamic function of volume-overloaded hearts from rats receiving propionyl-L-carnitine. A severe cardiac hypertrophy was induced in 2-mo-old rats by surgical opening of an aortocaval communication. Three months later, during in vitro perfusions with 1.2 mM palmitate, 11 mM glucose, and 10 IU/l insulin, the mechanical performance and overall energy turnover (myocardial O2 consumption) of hypertrophied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 0 publications
2
50
0
1
Order By: Relevance
“…Whether PARP inhibition exerts its beneficial effect in this model by affecting NAD/NADH levels or by other mechanisms (by reducing myocardial apoptosis or by limiting inflammatory processes) is not yet understood. Previous studies showed that cardiac NAD/NADH supply may change in hearts with mechanical overload, which was, in part, attributed to altered cellular metabolism (for example, oxidative utilization of glucose is slightly depressed in volume-overloaded hearts [ 108 ]. Yet, the role of NAD utilization by PARP in reducing NADH supplies remains to be explored.…”
Section: Evidence For Increased Poly(adp-ribose) Polymerase (Parp) Acmentioning
confidence: 99%
“…Whether PARP inhibition exerts its beneficial effect in this model by affecting NAD/NADH levels or by other mechanisms (by reducing myocardial apoptosis or by limiting inflammatory processes) is not yet understood. Previous studies showed that cardiac NAD/NADH supply may change in hearts with mechanical overload, which was, in part, attributed to altered cellular metabolism (for example, oxidative utilization of glucose is slightly depressed in volume-overloaded hearts [ 108 ]. Yet, the role of NAD utilization by PARP in reducing NADH supplies remains to be explored.…”
Section: Evidence For Increased Poly(adp-ribose) Polymerase (Parp) Acmentioning
confidence: 99%
“…The effects on glucose utilization, however, were more difficult to interpret in this study, because at high workloads the rates of glucose oxidation and lactate production were comparable in both groups, whereas at low workloads an increased rate of lactate production was observed in the hypertrophied heart. Likewise, in an experimental model of volumeoverload hypertrophy, palmitate oxidation was reduced and glucose oxidation unaffected, despite enhanced glycolysis [21,22]. It should be noted that the impaired oxidation of fatty acids was only evident when a long-chain fatty acid, i.e.…”
Section: Metabolic Remodelling During Cardiac Hypertrophymentioning
confidence: 99%
“…Indeed, it has been consistently observed that myocardial carnitine levels are reduced in hypertrophic hearts [22]. Secondly, the activity of several metabolic enzymes is modulated through protein phosphorylation.…”
Section: Metabolic Remodelling During Cardiac Hypertrophymentioning
confidence: 99%
“…In the adult heart, cardiac hypertrophy is associated with a reversion to a fetal metabolic profile (9,35) causing decreased fatty acid oxidation (1,12) and increased glycolytic rates (1,40,46). These metabolic changes correlate to altered expression/activity of key regulatory enzymes of energy substrate metabolism (2,13,21,44,45).…”
mentioning
confidence: 99%